The Possibility of Traffic Accidents Reconstruction Using Event Data Recorders – a Review - Đorđević, Branislav; Mitic, Sasa (Industrija, 2022)
Event Data Recorders (EDRs) have been used for the purpose of investigating traffic accidents for more than 20 years. Some countries have regulated their application by law, and they are valid evidence during investigations and reconstructions. However, recording devices are used as a source of certain data and information, as a supplement. Investigations using only recording devices are still not possible due to thesome phenomena that exist, and due to the constructional features of the devices. Scientists from Japan and Poland tested the accuracy of the data from the device and based on them performed reconstructions of accidents. Both teams have established that it is possible to perform reconstruction only in simple situations, such as a straight-line crash of one vehicle into another. When there are several participants in a crash, or a crash was preceded by a maneuver, it is not possible to determine what really happened. Further development of data recording devices is necessary, in order to increase their efficiency during the reconstruction of traffic accidents.
Keywords: Event Data Reorder, Crash test, Crash simulation, Reconstruction, Deviation.